Youth psychopathology: Universal or culture‐specific? Testing the syndrome models of youth self‐report in Chinese population. Issue 2 (30th September 2021) - Liu, Jianghong; Chan, Clare; Leung, Patrick W. L.
Abstract: Problem: The debate on whether psychiatric symptoms are universal and to what extent they are affected by culture is generally divided between the universalist and relativist approaches. Methods: This study compared Achenbach/Rescorla's model and Weisz's model of youth self‐report in 2521 Chinese adolescents (mean age = 12 years). Indigenous exploratory factor analyses were conducted to explore the factor structure of youth self‐report (YSR), and the derived models were tested with confirmatory factor analysis. Findings: These analyses indicated good support of the Chinese YSR models for males and females. Further analyses revealed three syndromes, namely anxious/depressed, somatic complaints, and aggressive behaviors, which represented broad internalizing and externalizing factors. These syndromes consistently demonstrated high correlations across the different models, indicating their universal nature. Conversely, some unique factors emerged in the Chinese YSR model, such as weight concern and rule‐breaking behavior, which may reflect underlying culture‐bound factors. Conclusions: Our findings support a combined perspective to the universalist and relativist approaches, which argues that some syndromes including Anxious/Depressed, Somatic Complaints, Aggressive Behavior and Attention Problems are more likely to be universal in male adolescents, while a new emerging syndrome like Weight Concern may reflect the socioeconomic, culture, and lifestyle changes that are currently emerging in China. Highlights: This study supports both the universalist and relativist approaches to assessing adolescent emotions and behavior. Specifically, the Chinese version of the youth self‐report (YSR) in our sample shows a good fit for both the universal Achenbach/Rescorla's model and culture‐specific Weisz's model. Some syndromes, like attention‐deficit/hyperactivity disorder and anxious/depressed, are more likely to be universal, while unique factors, such as weight concern and rule‐breaking behavior, emerged in the Chinese YSR model, which may reflect underlying culture‐bound factors. A combined perspective to the universalist and relativist approaches may be necessary for understanding adolescent behavior.